A double-hit pre-eclampsia model results in sex-specific growth restriction patterns - Violeta Stojanovska; Dorieke J. Dijkstra; Rebekka Vogtmann; Alexandra Gellhaus; Sicco A. Scherjon; Torsten Plösch (The Company of Biologists, 2019)
Pre-eclampsia is a multifactorial pregnancy-associated disorder characterized by angiogenic dysbalance and systemic inflammation; however, animal models that combine these two pathophysiological conditions are missing. Here, we introduce a novel double-hit pre-eclampsia mouse model that mimics the complex multifactorial conditions present during pre-eclampsia and allows for the investigation of early consequences for the fetus. Adenoviral overexpression of soluble fms-like tyrosine kinase (sFlt-1) and lipopolysaccharide (LPS) administration at mid-gestation in pregnant mice resulted in hypertension and albuminuria comparable to that of the manifestation in humans. A metabolomics analysis revealed that pre-eclamptic dams have increased plasma concentrations of phosphadytilcholines. The fetuses of both sexes were growth restricted; however, in males a brain-sparing effect was seen as compensation for this growth restriction. According to the plasma metabolomics, male fetuses showed changes in amino acid metabolism, while female fetuses showed pronounced alterations in lipid metabolism. Our results show that combined exposure to sFlt-1 and LPS mimics the clinical symptoms of pre-eclampsia and affects fetal growth in a sex-specific manner, with accompanying metabolome changes.